The Cooling Microclimate and Resulting Thermal Comfort of an Interstitial Fish Drying and Exterior Pavilion Space - Kim J.; Naboni E.; Garcia D. (Springer, 2023)
Half-dried, fermented fish is a significant part of the Faroe Islands’ historic cuisine, made possible through the archipelago’s unique environment. The fish drying process is at risk for future generations due to the lack of recorded quantitative data, as well as the effects of climate change. The climate of the Faroe Islands, while appropriate for fish drying, is not considered thermally comfortable. This study was conducted to enable a scientific understanding of fish drying and its suitable microclimate, and in parallel the thermal comfort offered by this environment to locals. Climatic and drying data were collected through an unheated, outdoor fish drying pavilion. To better understand the microclimatic conditions, (created or required by) the drying process, and the resulting thermal comfort, the climatic conditions were recorded throughout the study period and occupants of the pavilion were surveyed. Fish were hung in different microclimatic zones with the experiment results showing a 27% and 40% water loss after seven and twelve days of drying, respectively. Majority of surveyed participants and the calculated thermal comfort metrics both found the pavilion microclimate to provide an increase in thermal comfort compared to the exterior conditions.